If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(2z + 3) + -1 = 0 Reorder the terms: 12(3 + 2z) + -1 = 0 (3 * 12 + 2z * 12) + -1 = 0 (36 + 24z) + -1 = 0 Reorder the terms: 36 + -1 + 24z = 0 Combine like terms: 36 + -1 = 35 35 + 24z = 0 Solving 35 + 24z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 24z = 0 + -35 Combine like terms: 35 + -35 = 0 0 + 24z = 0 + -35 24z = 0 + -35 Combine like terms: 0 + -35 = -35 24z = -35 Divide each side by '24'. z = -1.458333333 Simplifying z = -1.458333333
| 9x^2+6x+1=81 | | 4/5+9y/2=4/3+9y/4 | | -1/12x=-9 | | 49.14/2 | | 6x^2+13x-20=0 | | -6x-20=20 | | -8+8z-6z=-12 | | z+37=21 | | 3x+6=5x+1 | | -12+6z=-66 | | 9x/5-11/3=-9/7-x | | 4t-2=2 | | -(-14x+25)-21-19x=23x+20 | | 27+7z=-6z+28z-23 | | 2x^2-20x-48=0 | | -8(y-7)=4y-40 | | -5y/4-6/5=7/3 | | 4r^2+24r=-17 | | -5(2x+3)=15 | | .18-.33= | | 2x^2-19x-6=0 | | 4x^3-16x^2-9x-36=0 | | -5(3z+3)=-3(5z-4) | | 3+3y/2=7/2 | | 1/5x+2/3=-4/5x-1/6 | | 5(2g-3)-6g=-2(g-6)+3 | | 3x^2-45x+4x-60=0 | | 2x^2+4x=9x-18 | | 9x+12=48 | | 12=m/7+3 | | 4(8x+6)=-7(3x-4)+5x | | 30=3(w-5)+6w |